Ares del Maestrat a finals del segle XIX: estructura de la riquesa i classes socials - Forner i Valls, Enric (Millars. Espai i Història, 2018)
Study of the economic and socialstructure of a mountainous interior municipality, of the poor dryness in the second ha lf of the XIXth century: Ares del Maestre (Alt Maestrat), through fiscal documents interrelated with other sources to establish their coherence, which permis to know the economic features of the people and their sources of income. It is analysed the distribution of the wealth that is detached of the fiscal documents, in monetary and relative terms, as well as of the properly of the land, in physical units. On these bases it is tested a characterization of the social classes.